Significance of L2 and L3 Motivation in the Context of an English-Taught Program: A Preliminary Study at a Japanese University - Naoko Kojima (MDPI AG, 2023)
This study explores the motivation of international students who simultaneously studied L2 English and L3 Japanese while learning in an English-taught program specializing in policy studies at a Japanese university. Data were collected from five participants using semi-structured interviews, motivation graphs, a biographical questionnaire, and the program's application form to examine how international students chose the program and the trajectories of their motivations to learn English, Japanese, and policy studies. The results show that all participants had rich experience in learning English and/or intercultural contacts before coming to Japan. Although two participants wanted to live in Japan to learn the language, three had no specific aim of studying abroad. The students' motivation to learn English was enhanced when their study became more advanced, but their motivation to learn Japanese was more varied and complex. Although sustaining the motivation to learn Japanese over time seemed demanding, one of the participants invested more time in learning Japanese than English. This study highlights that exploring students' disposition of motivation and international orientation can be beneficial, especially in uncovering why and how students can sustain their motivation to learn Japanese for academic purposes. Furthermore, it could indicate future directions for such programs.